Engineering data on mixing - Mezaki, Reiji; Mochizuki, Masafumi; Ogawa, Kohei; ScienceDirect eBooks (Amsterdam ; New York : Elsevier, 2000)
This book is a compilation of the engineering data on mixing, which have appeared in the major technical journals of chemical engineering and bioengineering since 1975. That year marked the beginning of a period of rapid advancement in the science and technology of mixing, with rather reliable results for both theoretical and experimental studies. In addition, some important earlier articles which have been, and still are being referred to, are included. Designs of both agitators and tanks still depend primarily on art and experience. In light of this it was felt that the data on mixing should be compiled and presented in a systematic manner to assist in design and analysis of agitated tanks, and to provide easier access to mixing data for various engineering activities. Although computer-aided searches of pertinent data bases can be of assistance to chemical engineers and bioengineers in their studies, they are sometimes time-consuming and often costly. Furthermore inadequate selection of key words can jeopardize the searches. This book offers an alternative method of surveying mixing data which interests readers. The first chapter presents a variety of results for the experimental measurements of flow patterns in stirred tanks. Most of the measurements were made by using modern Laser-Doppler techniques. This chapter is useful for the prediction of flow patterns in tanks with many different geometries, various types of agitators, and fluids of diverse physical and rheological properties, plus valuable data for the validation of results obtained by CFD simulations. Chapters 2 through 5 deal with data for traditional chemical engineering subjects and Chapter 6 summarizes a number of scale-up relations developed over the years for various systems. These include liquid, solid-liquid, liquid-liquid, gas-liquid, and solid-liquid-gas systems. Chapter 7 provides data related to multiphase processes, and most importantly, drop size and drop-size distributions and bubble-size distributions. These two subjects have not been treated systematically either in text books or in handbooks on stirred-tank mixing, although the results of both experimental and theoretical investigations have been reported on many occasions. Finally gas-inducing mechanically agitated systems are dealt with. The applications of this type of agitation system will become increasingly attractive from the standpoint of rationalization of stirred-tank operations as well as environmental protection.
Chapter headings: Flow Patterns. Mixing Time. Power Draw and Consumption. Heat Transfer. Mass Transfer. Scale-up Rules. Other Subjects Related to Multi-phase Systems. Gas-inducing Mechanically Agitated Systems.
Includes index.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Keywords: Mixing; Mixing; Mélange.; Electronic books